Digital literacy competency indicator for Indonesian high vocational education needs - Sintha Wahjusaputri; Tashia Indah Nastiti (Intelektual Pustaka Media Utama, 2022)
In the face of the COVID-19 pandemic, education in Indonesia has shifted from face-to-face learning to online learning via the internet and digital technology. Therefore, digital literacy is a skill needed by vocational students and teachers today. This study aimed to identify and analyze digital literacy competency indicators to improve the quality of learning in high vocational education. This research employed a systematic review method, especially a qualitative meta-ethnographic approach, by reviewing various studies related to digital literacy competencies from various journal articles and conferences to then carry out the synthesis process. Meta-ethnography as part of the systematic review method integrates data across studies to obtain new theories and concepts with a deeper and more thorough understanding. The results showed four competency factors and 28 indicators to improve digital literacy competence. This research can be the basis of creating a digital literacy assessment model for high vocational education in Indonesia.